Improving the Physical and Chemical Properties of a Disturbed Soil Using Drying-bed Biosolids. Issue 11 (16th June 2016) - Sloan, John J.; Ampim, Peter A.Y.; Boerth, Thomas; Heitholt, James J.; Wu, Yingzhe
ABSTRACT: Disturbed soils might be improved by increasing organic matter content. The objective of this study was to determine if a large application of drying-bed biosolids would improve soil productivity and promote bermudagrass ( Cynodon dactylon ) and establishment on the Trinity clay soil. Anaerobically digested, air-dried biosolids were applied to Trinity clay (very-fine, montmorillonitic, thermic, typic, pelludert) at rates of 0, 112, 560, and 1120 Mg ha −1 . The biosolids were incorporated into the top 15 cm of the soil and bermudagrass sprigs were planted. Biosolids significantly reduced soil bulk density and soil resistance to penetration when measured during the second and third years after the application. Biosolids increased soil concentrations of organic carbon, nutrients (nitrogen, phosphorus, copper, zinc, iron) and heavy metals (cadmium, chromium, nickel, lead). Bermudagrass biomass production and nutrient uptake were increased due to biosolids, but heavy metals were not significantly transferred from soil to above-ground plant tissue.